(untitled) (Al-Qamar, 2023)
In this paper, articles from Higher Education Commission approved journals based on the concept of ethics in the Bible and the Qurʼan have been reviewed. Ethic refers to the behavior that is based on morals. The position of ethics is like a backbone in any nation and society. The common chapter of the religions of the world is ethics on which there is no disagreement. A review of the concept of ethics reveals that the word ethics does not exist at all in the Hebrew Bible. But through preliminary evaluations the meaning of ethics is understood. In the Hebrew Bible, God’s will be considered moral. Unlike other religions, in Islam apart from worship, morals are of key importance. Moral principles and duties are briefly discussed in the Bible. However, the Qurʼan provides complete guidance on moral principles and rules. After presenting the introduction of the articles in this paper, the summary of these articles is then presented at the end of the analysis of all the articles.